O ensino de álgebra e os registros de representação semiótica: um olhar para a prática dos professores do 8º ano do ensino fundamental - Langwinski, Luani Griggio (2018)
This is a qualitative research of a comprehensive nature; its objective was to understand and analyze how the teacher mobilizes the algebraic registers in Mathematics classes of the 8th year of Basic Education. The research was done in state schools in Santa Terezinha de Itaipu/PR, Brazil, to identify and understand the approaches of the teaching of Algebra used by the teachers for the formalization of this teaching. The instruments used for the data collection were the semi-structured interview, observations and filming of the observed classes and the field diary. We adopted Raymond Duval's Theory of Semiotic Representation Registers (TRRS) as a reference to assist in the analysis and discussion of data. We investigate the introduction of Algebra teaching; we observe the mathematical contents: algebraic expressions, division and potentiation of monomials, operations of addition, subtraction, multiplication and division of polynomials and notable products. From the analysis of the representation registers used, produced and elaborated by the teachers, it is worth noting that: there is an effort on the part of the teachers to minimize the difficulties of the students, for that they make analogies, in which the geometric and numerical representations stand out. Despite this, we note the emphasis given to algebraic treatment. As a conclusion, we emphasize that the different registers used by teachers make possible a better understanding of the content taught, however, especially, the care with the spoken register and the relation between the meaning given by the teacher and the significance assigned by the student must always be objects of attention.